Mahathir predicts election not long from now - Borneo Post, (KK) (The Borneo Post, 2012)
SINTOK: Former prime minister Tun Dr. Mahathir Mohamad said yesterday he feels that the 13th general election will be held soon as the situation "look good" for the ruling coalition.